Uncovering the role of wheat magnesium transporter family genes in abiotic responses - Tang, Yanhong; Yang, Xiaoyue; Li, Han; Shuai, Yating; Chen, Wang; Ma, Dongfang; Lü, Zhichuang (Frontiers in Plant Science, 2023)
Background The CorA / MGT / MRS2 family proteins are an important group of magnesium transporter proteins that maintain magnesium ion homeostasis in plant cells. However, little is known about the MGT functions in wheat. Methods The known MGT sequences were used as queries to BlastP against wheat genome IWGSC RefSeq v2.1 assembly (E-value <10–5). Chromosome localization information for each TaMGT gene was obtained from the GFF3 file of the wheat genome data (IWGSCv2.1).The sequence of 1500 bp upstream of the TaMGT genes was extracted from the wheat genome data. The cis-elements were analyzed using PlantCARE online tool. Result A total of 24 MGT genes were identified on 18 chromosomes of wheat. After functional domain analysis, only TaMGT1A, TaMGT1B, and TaMGT1D had GMN mutations to AMN, while all the other genes had conserved GMN tripeptide motifs. Expression profiling showed that the TaMGT genes were differentially expressed under different stresses and at different growth and development stages. The expression levels of TaMGT4B and TaMGT4A were significantly up-regulated in cold damage. In addition, qRT-PCR results also confirmed that these TaMGT genes are involved in the wheat abiotic stress responses. Conclusion In conclusion, The results of our research provide a theoretical basis for further research on the function of TaMGT gene family in wheat.